Epitranscriptomic modifications in acute myeloid leukemia: m6A and 2′-O-methylation as targets for novel therapeutic strategies - Pauli, Cornelius; Kienhöfer, Michael; Göllner, Stefanie; Müller-Tidow, Carsten (Biological chemistry, 2021)
Modifications of RNA commonly occur in all species. Multiple enzymes are involved as writers, erasers and readers of these modifications. Many RNA modifications or the respective enzymes are associated with human disease and especially cancer. Currently, the mechanisms how RNA modifications impact on a large number of intracellular processes are emerging and knowledge about the pathogenetic role of RNA modifications increases. In Acute Myeloid Leukemia (AML), the N 6 -methyladenosine (m 6 A) modification has emerged as an important modulator of leukemogenesis. The writer proteins METTL3 and METTL14 are both involved in AML pathogenesis and might be suitable therapeutic targets. Recently, close links between 2′- O -methylation (2′- O -me) of ribosomal RNA and leukemogenesis were discovered. The AML1-ETO oncofusion protein which specifically occurs in a subset of AML was found to depend on induction of snoRNAs and 2′- O -me for leukemogenesis. Also, NPM1, an important tumor suppressor in AML, was associated with altered snoRNAs and 2′- O -me. These findings point toward novel pathogenetic mechanisms and potential therapeutic interventions. The current knowledge and the implications are the topic of this review.
Gesehen am 05.01.2022